Vodcasting and specialised film journalism. A new media for reflection on the seventh art - Cartes-Barroso, Manuel J. (Documentación de las Ciencias de la Información, 2025)
The cinema, an art and a discipline with great relevance for citizens since its birth at the end of the 19th century, is currently an area of journalistic specialisation within the field of Culture, with an extensive trajectory that goes beyond its presence in traditional media or in specific journalistic genres such as film criticism. The incorporation of the Internet has made possible the emergence of new opportunities for film journalism, which can also be consumed on social media and platforms such as video podcasting. This is the case of RTVE's vodcast ‘El último programa’, where its presenters —three film critics and expert journalists— analyse and reflect on contemporary films available on the digital platform of Spain's public audiovisual corporation. And they do so with a varied number of thematic contents, connecting ideas, stories and films. Among the results, we observe an adequate work of editing, production and audiovisual production, which denotes the good work of a technical and human team at a professional level. In conclusion, thanks to its close style and touches of humour, ‘El último programa’ is presented as a different programme from the reality of video podcasting, which is also a new journalistic narrative for lovers of the seventh art.
Keywords: vodcasting; specialised journalism; film criticism; cinema; audiovisual journalism; digital video